Holt-Oram syndrome (analysis of six cases) - Tunçbilek, Ergül; Özme, Şencan; Besim, Aytekin; Balcı, Sevim (The Turkish Journal of Pediatrics, 1980)
Six cases radiologically and clinically diagnosed Holt-Oram Syndrome are reported. Two of the cases are familial and the others are caused by de novo mutation. One, has preaksial polydactyly which is an uncommon finding in this syndrome.